2016
DOI: 10.1073/pnas.1519061113
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in genetic selection differentials and generation intervals in US Holstein dairy cattle as a result of genomic selection

Abstract: Seven years after the introduction of genomic selection in the United States, it is now possible to evaluate the impact of this technology on the population. Selection differential(s) (SD) and generation interval(s) (GI) were characterized in a four-path selection model that included sire(s) of bulls (SB), sire(s) of cows (SC), dam(s) of bulls (DB), and dam(s) of cows (DC). Changes in SD over time were estimated for milk, fat, and protein yield; somatic cell score (SCS); productive life (PL); and daughter preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
360
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(416 citation statements)
references
References 47 publications
17
360
0
9
Order By: Relevance
“…The use of GS for accelerating genetic gains, based on genomic-estimated breeding values predicted using genome-wide dense markers, has been deployed extensively in dairy cattle (Van Raden et al, 2009). García-Ruiz et al (2016) reported a positive impact of GS on cattle breeding through drastic reduction of generation interval and increased selection intensity for low heritable traits. Initially, computer simulations and parametric and non-parametric statistical models were used on maize and wheat datasets to study the prediction accuracies in real plant breeding scenarios (Bernardo and Yu, 2007;de los Campos et al, 2009;Crossa et al, 2010Crossa et al, , 2011.…”
Section: Genomic Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of GS for accelerating genetic gains, based on genomic-estimated breeding values predicted using genome-wide dense markers, has been deployed extensively in dairy cattle (Van Raden et al, 2009). García-Ruiz et al (2016) reported a positive impact of GS on cattle breeding through drastic reduction of generation interval and increased selection intensity for low heritable traits. Initially, computer simulations and parametric and non-parametric statistical models were used on maize and wheat datasets to study the prediction accuracies in real plant breeding scenarios (Bernardo and Yu, 2007;de los Campos et al, 2009;Crossa et al, 2010Crossa et al, , 2011.…”
Section: Genomic Selectionmentioning
confidence: 99%
“…The impact of GS and generation intervals in cattle breeding was first systematically studied by de Roos et al (2010). Recently, García-Ruiz et al (2016) reported that decreased generation interval and increased selection intensity for low heritable traits is as a result of the positive impact of GS on the US cattle industry. Genomic selection in combination with a reduced generation interval may double the rate of genetic gain while keeping the rate of inbreeding per generation constant.…”
Section: Selection Intensity and Generation Intervalmentioning
confidence: 99%
“…This was the first species where GS was applied due to its peculiar population structure, since GS can be quite effective in reducing the long generation interval in dairy cattle (García-Ruiz et al 2016). Currently, GS is being extended to other species.…”
mentioning
confidence: 99%
“…Nowadays, fertility is included in national selection index of many countries (Miglior et al, 2005) and improvement on daughter pregnancy rates has been found from the use of genomic selection (García-Ruiz et al, 2016). However, selection for improved fertility is a complex task.…”
Section: Introductionmentioning
confidence: 99%